Ketimpangan ekonomi dan akses kesempatan: studi terhadap mobilitas sosial generasi muda di indonesia - Farhatin, Farhatin (Maliki Interdisciplinary Journal, 2025)
The social mobility of young people in Indonesia is influenced by economic inequality, which is primarily caused by unequal access to education and economic opportunities, which reinforces cycles of poverty and limits opportunities to improve socio-economic status. This article examines how inequality in access to education and economic opportunities impacts social mobility among Indonesian youth. It also explains its positive and negative effects. To create more equitable social mobility, the study suggests more inclusive policies that increase access to education and employment opportunities.